(untitled) (International Journal of Innovative Computing, 2019)
Nowadays, research and development of Underwater Wireless Sensor Networks (UWSNs) widely supporting various available application such as oil/gas monitoring system, tsunami monitoring, disaster prevention, and environmental monitoring has become increasingly popular among academicians and industries. However, to develop efficient communication in UWSNs is a difficult duty due to the irregular nature of the underwater environment. In our previous review [14], we did an elaborate theoretical survey on UWSNs routing protocols. In this work, we are going to evaluate the performance of some of the UWSNs routing protocols under high-density network condition. To simulate a high-density UWSNs, we are placing hundreds of underwater nodes in a small three-dimensional topographical area and study the behavior of the routing protocol and the network. We have chosen to evaluate some of the frequently addressed underwater routing protocols such as Underwater Flooding (UWFlooding), Vector-Based Forwarding (VBF), and Hop by Hop Vector-Based Forwarding (HH-VBF) under this high-density network scenarios. The result of our study shows that VBF and HH-VBF perform better in term of the number of packets received, dropped packets and PDR, while UWFlooding performs better in term of cumulative delay.